Utilization of extracellular polymeric substances (EPS) immobilized in epoxy polymer as double ion exchanger biosorbent for removal of chromium from aqueous solution - Kistriyani, Lilis; Salimin, Zainus; Chafidz, Achmad (Communications in Science and Technology, 2020)
Cation and industrial pollutant anions are removed from wastewater using organic cation and anion exchange resin. "Extracellular Polymeric Substance" (EPS) from bacterial extraction can accumulate cation and anion elements through biosorption by adsorption mechanism, ion exchange, formation of complex compounds and hydrogen bonds. EPS can be used as an biosorbent and ion exchange bioresin replacing organic resins, because EPS contains organic functional groups that are negatively charged (RCOOH, ROPO3H, ROPO3Na, ROSO3H, ROSO3Na, etc.) cation absorbers and positively charged (ROH, RCNH2HCOOH, etc.) anion absorber. EPS consists of 40-95% polysaccharide compounds, protein 1-60%, nucleic acids 1-10%, lipids 1-10% and the remaining amino acid polymers and other compounds. The tannery industry produces trivalent (Cr+3) chromium pollutants at levels of 15.2 ppm and hexavalent (CrO4-2 or Cr2O7-2) levels of 0.77 ppm which exceeds the standard quality for a total Cr of 0.6 ppm. Cr pollutants are very dangerous for human health. Research had been done on the use of immobilized EPS bioresin in epoxy polymers for chromium binding. EPS was extracted from bacterial activated sludge by centrifugation at 9000 rpm for 20 minutes at 4°C, the filtrate was EPS. The analysis showed EPS content were 16% fat, 12% carbohydrate, and 16% protein. The functional group analysis results with infrared ray spectroscopy (FTIR) showed EPS containing chemical bonds such as -CH, -OH, -NH, and -C=O which proved that EPS extraction contained RCOOH, ROH, and RCNH2HCOOH functional components which were exchanging components cations and anions. Epoxy polymers were prepared by mixing bisphenol A monomers and 1: 1 ratio epichlorohydrin. Immobilized EPS double ion exchange biorecin in epoxy polymers was prepared by mixing 200 mg EPS and 1800 mg epoxy. The binding of chromium ions in the resin was carried out by recirculating the chromium solution through a burette column filled with 2 rams of bioresin at pH 5, 6 and 7. The optimum results gave chromium ion absorption efficiency of 89.20% at pH 5. Column operations could be optimized by varied the amount of bioresin used.